(untitled) (Global Journals of Research in Engineering, 2013)
This paper is devoted to make use of the boundary element method as a practical problem solving tool to analyze the soilpile interaction problems. A computer program was adopted for the analysis process. It is a computer package called PGroupN which is concerned mainly with the analysis of the pile group problems. A non-linear soil model has been adopted with this program to assess the pile-soil interaction within the group. Some parametric studies were carried out with this problem including the pile diameter, pile length, spacing to diameter ratio, soil type (sand) and the thickness of stratum. It was found that for 9 pile group analyzed, the corner pile carries about 4% more than the average load, while the border and the center piles carry 2% and 10% less than the average load, respectively. As the ratio of pile spacing to diameter (S/D) increases, the difference between loads on each pile decreases, especially between the corner and the center piles